SYNTHESIS OF THINNED LINEAR AND PLANAR ANTENNA ARRAYS USING BINARY PSO ALGORITHM - Wang, Wei-Bo; Feng, Quanyuan; Liu, Dong (Electromagnetic waves (Cambridge, Mass.), 2012)
Traditional optimization methods are not well suitable for thinning large arrays to obtain a low sidelobe level (SLL). The chaotic binary particle swarm optimization (CBPSO) algorithm is presented as a useful alternative for the synthesis of thinned arrays. The proposed algorithm can be improved by nonlinear inertia weight with chaotic mutation to increase the diversity of particles. Two examples have been presented and solved. Simulation results are proposed to compare with published results to verify the effectiveness of the proposed method for both linear and planar arrays.